Pembangunan Sistem Informasi Praktik Kerja Lapangan Berbasis Web - Viona Febriana; Ibnu Santoso (Politeknik Statistika STIS, 2022)
BPS Malang City organizes street vendors activities with a limit of 16 participants per day. The system of registration, attendance, and recording of street vendors' daily activity reports is still done conventionally. This causes the registration process to be inefficient. In addition, there are errors in the calculation of attendance and the daily activity reports are not well documented. So that street vendors' activities can run effectively and efficiently in line with current technological developments, researchers plan to build a web-based street vendor information system that provides registration information, attendance and daily activity reports. The method used is the System Development Life Cycle (SDLC) waterfall model, using the Codeigniter 4 framework. The black-box test results show that all system features can run as expected. The final score of usability evaluation using the System Usability Scale (SUS) is 74,791. This indicates that the PKL information system built at BPS Malang is included in the Acceptable category and can be well received by users.